The non-linear correlation between the severity of alcohol consumption and depressive symptoms in the Chinese Wa ethnic minority - Liu, Junjun; Feng, Xiaotang; Liu, Yang; Xiao, Libin; Tong, Ruixiang; Wang, Yangchun; Lu, Zhaomin; Jia, Fengnan; Zhang, Xiaobin; Li, Zhe; Du, Xiangdong; Yang, Wanqiu (Frontiers in Public Health, 2024)
ObjectiveThe aim of this research was to examine the association between alcohol consumption and depressive symptoms in the Wa ethnic minority of China, a population where this relationship has been insufficiently explored.MethodsA cross-sectional analysis was conducted on a sample of 317 current drinkers from the Wa ethnic minority, a “direct fast-forward” group in Cangyuan County, between December 1, 2022, and February 28, 2023. Utilizing a multi-stage cluster sampling approach, participants were selected, each of whom exhibited an Alcohol Use Disorder Identification Test (AUDIT) score exceeding 0. Data were collected via face-to-face interviews employing a uniform questionnaire. Quantification of alcohol use was achieved through the application of the AUDIT, while the Patient Health Questionnaire (PHQ)-9 was employed to gauge depressive symptoms. The relationship between the severity of alcohol consumption and depressive symptoms was evaluated using a multivariable logistic regression model. Subsequently, potential non-linear associations were scrutinized through the application of a smoothing plot.ResultsThe study included 317 current drinkers (196 males [61.83%]; mean age 41.78 ± 12.91 years), of which 94 (29.65%) exhibited comorbid depressive symptoms. Multivariable logistic regression analysis, adjusting for confounders, revealed that higher AUDIT scores were significantly associated with an increased probability of depressive symptoms (OR = 1.09, 95% CI: 1.02–1.18, p = 0.008). The risk of depressive symptoms was notably greater in the group with alcohol dependent range in contrast the group at low-risk range (OR = 7.01, 95% CI: 1.66–29.62, p = 0.008). The smoothing plot indicated a J-shaped non-linear relationship with an inflection point at an AUDIT score of 15. To the left of this inflection point, no significant relationship was observed, whereas to the right, a positive correlation emerged (OR = 1.39, 95% CI: 1.11–1.74, p < 0.001).ConclusionThe findings reveal a non-linear relationship between alcohol consumption and the probability of depressive symptoms within the Wa ethnic minority in China, with implications for the development of nuanced and effective treatment strategies tailored to this population.